IMPLEMENTASI KEPEMIMPINAN ADAPTIF KEPALA SEKOLAH DALAM MENGELOLA TANTANGAN ADAPTIF GURU DI SEKOLAH DASAR - Dani Darmawan; Yari Dwikurnaningsih; Herry Sanoto (STKIP Subang, 2026)
This study aims to analyze the implementation of adaptive leadership by a school principal in managing teachers’ adaptive challenges in an elementary school. The research employed a qualitative approach with a single case study design. The participant was a principal selected purposively as the key informant. Data were collected through semi-structured in-depth interviews and documentation, and analyzed using thematic analysis supported by MAXQDA software and the Miles and Huberman interactive analysis model. Data credibility was ensured through member checking. The findings indicate that the implementation of adaptive leadership is characterized by the dominant practices of holding environment, giving the work back, and protecting voices from below. The principal created a psychologically safe space for dialogue, actively involved teachers in problem solving, and protected diverse perspectives within the organization. The challenges faced by teachers were not only technical but also adaptive, particularly related to mindset changes in inclusive education practices. Resistance appeared in the form of anxiety and professional uncertainty, which were managed through open communication and collaboration. The study concludes that adaptive leadership is effective when it emphasizes psychological safety, collective participation, and teacher empowerment as agents of change. These findings contribute to strengthening school leadership practices that are responsive to the complexity of educational change